Black unionism in the industrial South - Obadele-Starks, Ernest, 1959- (Texas A & M southwestern studies, 2000)
"Black Unionism in the Industrial South presents the struggles of black workers who fought for equality and unionization in the heyday of Gulf Coast industry. Ernest Obadele-Starks examines the workers' responses to racial and class domination and their creative strategies to reach their goals. Facing public and corporate policies that typically deferred to white workers, blacks banded together to achieve representation in the workplace, form union auxiliaries, charter their own local unions, seal alliances with members of the black middle class, and manipulate the media to benefit their cause."--Jacket